Given the equation:
3x + 4y = -4
Let's graph the line that represents the equation above.
To grah the line, rewrite the equation in slope-intercet form:
y = mx + b
Where m is the slope and b is the y-intercept.
Rerite the equation for y:
3x + 4y = -4
Subtract 3x from both sides:
3x - 3x + 4y = -3x - 4
4y = -3x - 4
Divide all terms by 4:
![\begin{gathered} (4y)/(4)=-(3x)/(4)-(4)/(4) \\ \\ y=-(3)/(4)x-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/dnz2zb1yc83ps2438fnak975d2wfbaup8z.png)
The slope of the line is -3/4, while the y-intercept is at (0, -1).
Now, let's graph the line using 3 points.
• When x = -4:
Substitute -4 for x and solve for y
![\begin{gathered} y=-(3)/(4)\ast(-4)-1 \\ \\ y=3-1 \\ \\ y=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/svsbpnw46ghrbyz0md93r6bztw81rlt3l8.png)
• When x = 0:
Substitute 0 for x and solve for y
![\begin{gathered} y=-(3)/(4)\ast(0)-1 \\ \\ y=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/kzngir8mot8ua9l8vsx7a5vpq752muoh3o.png)
• When x = 4:
Substitute 4 for x and solve for y
![\begin{gathered} y=-(3)/(4)\ast4-1 \\ \\ y=-3-1 \\ \\ y=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/6bunnbboqe2h3xhe448vebwmnkea426i0m.png)
Therefore, we have the following points:
(-4, 2), (0, -1) and (4, -4)
Plot the three points on the graph, then connect all 3 points using a straight edge.
We have the graph attached below: